Assessing Project-Level Grievance Redress Mechanisms Using a Human-Rights-Based Approach : Tips and Tools - World Bank (Washington, DC : World Bank, 2022)
This note is a resource for World Bank task teams providing technical assistance to Borrowers on grievance redress mechanisms (GRMs). The first step in strengthening a project-level GRM, after discussing it within the task team and informing the Country Management Unit (CMU), is to organize a technical assistance mission to conduct a detailed GRM diagnostic for the project or group of projects selected. This helps the project implementation unit (PIU) and task team understand the PIU’s capacity for grievance management, learn about grievance resolution experiences of PIU staff and potential complainants and project beneficiaries through field visits, share international experiences with grievance redress while building the capacity of relevant staff, and facilitate the preparation of a GRM strengthening action plan by relevant PIU counterparts. The guidance and tools provided here, including templates and worksheets, can help social development specialists and other relevant task team members systematically plan and organize such missions.